Iron entry in neurons and astrocytes: a link with synaptic activity - Codazzi, Franca; Pelizzoni, Ilaria; Zacchetti, Daniele; Grohovaz, Fabio (Frontiers in Molecular Neuroscience, 2015)
Iron plays a fundamental role in the development of the central nervous system (CNS) as well as in several neuronal functions including synaptic plasticity. Accordingly, neuronal iron supply is tightly controlled: it depends not only on transferrin-bound iron but also on non-transferrin-bound iron (NTBI), which represents a relevant quote of the iron physiologically present in the cerebrospinal fluid (CSF). Different calcium permeable channels as well as the divalent metal transporter 1 (DMT1) have been proposed to sustain NTBI entry in neurons and astrocytes even though it remains an open issue. In both cases, it emerges that the control of iron entry is tightly linked to synaptic activity. The iron-induced oxidative tone can, in physiological conditions, positively influence the calcium levels and thus the synaptic plasticity. On the other hand, an excess of iron, with the ensuing uncontrolled production of reactive oxygen species (ROS), is detrimental for neuronal survival. A protective mechanism can be played by astrocytes that, more resistant to oxidative stress, can uptake iron, thereby buffering its concentration in the synaptic environment. This competence is potentiated when astrocytes undergo activation during neuroinflammation and neurodegenerative processes. In this minireview we focus on the mechanisms responsible for NTBI entry in neurons and astrocytes and on how they can be modulated during synaptic activity. Finally, we speculate on the relevance they may have in both physiological and pathological conditions.